PENERAPAN FATWA DSN-MUI NOMOR 25 DAN 26 TAHUN 2002 DI PEGADAIAN SYARIâAH KUSUMANEGARA YOGYAKARTA - Sodriyatun, Sodriyatun (Islamic University of Indonesia, 2010)
This article suggests that formal judicial Pawnshop Yogyakarta Shariah Board of Directors established under Decree Pawnshop on the translation of Government Regulation no. 103 of 2000 on Pawnshop, so do not yet have specific rules about pawn in the form of Sharia Law. The existence of the National Fatwa Council of Sharia - the Indonesian Ulema Council No. 25 and 26 as well understood as the juridical basis for the formal operation of Sharia Pawnshop Yogyakarta. Pawnshop Shariah Yogyakarta is an independent unit of Pawnshop which is the result of collaboration between the Bank Muamalah Pawnshop Indonesia. Pawnshop service products Yogyakarta Shariah compliance in accordance with the principles of Shariah fatwa charge of the National Shariah Council - the Indonesian Ulema Council which became operational basis, but still very limited compared with mortgage services products in general, there are no new creations of business development services to answer the needs of the community.